PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBM) UNTUK MENINGKATKANHASIL BELAJAR IPA SISWA KELAS IV SDS AISYIYAH BENGKALIS - Nilaksum '; Syahrilfuddin '; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the poor performance of fourth graders studying SDS Aisyiyah Bengkalis. Detailed criteria Minimum Value (KKM) school science set 65.00. Among the students who totaled 23 people, only 10 people (43.48%), which reached the KKM, whereas 13 patients (56.52%) who have not reached the KKM, with an average value of 62.17. This research is a classroom action research (CAR) conducted aims to improve learning outcomes in grade IV grade science students SDS Aisyiyah Bengkalis by applying the Problem Based Learning Model. The activities of teachers in cycle I of my meeting a percentage of 60.00% gain enough categories, at the second meeting the cycle I increased with the percentage of 70.00% both categories. Furthermore, the first meeting of the cycle II of the teacher's activities increase the percentage of 80.00% in the excellent category and at the second meeting the cycle II increased again with a percentage of 95.00% is a very good category. Student activities at the first meeting cycle I of obtaining a sufficient percentage of the category of 55.00%, in the second meeting of cycle I increased percentage of 65.00% to the good category, at the first meeting of th cycle II increased by a percentage of 80.00% is a very good category. At the second meeting of the cycle II increased with the percentage of 90.00% is a very good category. From the results of the study before action Average 62.17 increase to 63.91 in Cycle I. In cycle II increased 71.43. Keywords: Model Based Learning Problem (BLP), Natural Science Learning Outcomes